Effect of Cup Feeding and Bottle Feeding on Breastfeeding in Late Preterm Infants: A Randomized Controlled Study. (May 2014) - Yilmaz, Gonca; Caylan, Nilgun; Karacan, Can Demir; Bodur, İlknur; Gokcay, Gulbin
Background: Cup feeding has been used as an alternative feeding method for preterm infants. Objective: The purpose of this study was to determine the effect of bottle and cup feeding on exclusive breastfeeding rates at hospital discharge and 3 and 6 months post-discharge in late preterm infants. Methods: Included in the study were preterm infants of 32 to 35 weeks' gestation fed only by intermittent gastric tube at the time of recruitment; 522 infants were randomly assigned to 2 groups: the cup-fed group (n = 254) and bottle-fed group (n = 268). Main outcomes were prevalence of exclusive breastfeeding at discharge and 3 and 6 months after discharge, and length of hospital stay. Results: Infants randomized to cup versus bottle feeding were more likely to be exclusively breastfed at discharge home (relative risk [RR], 1.58; 95% confidence interval [CI], 1.36-1.83), 3 months after discharge (RR, 1.64; 95% CI, 1.42-1.89), and 6 months after discharge (RR, 1.36; 95% CI, 1.14-1.63). There was no significant difference between groups for length of hospital stay. The mean hospital stay was 25.96 ± 2.20 days in the bottle-fed group and 25.68 ± 2.22 days in the cup-fed group. There was no significant difference between groups for time spent feeding, feeding problems, or weight gain in hospital. Conclusion: Cup feeding significantly increased the likelihood of late preterm infants being exclusively breastfed at discharge and 3 and 6 months after discharge, and cup feeding did not increase the length of hospital stay. Overall, we recommend cup feeding as a transitional method prior to breastfeeding for late preterm infants during hospitalization.